Impact of Leishmania metalloprotease GP63 on macrophage signaling - Isnard, Amandine; Shio, Marina T.; Olivier, Martin (Frontiers in Cellular and Infection Microbiology, 2012)
The intramacrophage protozoan parasites of Leishmania genus have developed sophisticated ways to subvert the innate immune response permitting their infection and propagation within the macrophages of the mammalian host. Several Leishmania virulence factors have been identified and found to be of importance for the development of leishmaniasis. However, recent findings are now further reinforcing the critical role played by the zinc-metalloprotease GP63 as a virulence factor that greatly influence host cell signaling mechanisms and related functions. GP63 has been found to be involved not only in the cleavage and degradation of various kinases and transcription factors, but also to be the major molecule modulating host negative regulatory mechanisms involving for instance protein tyrosine phosphatases (PTPs). Those latter being well recognized for their pivotal role in the regulation of a great number of signaling pathways. In this review article, we are providing a complete overview about the role of Leishmania GP63 in the mechanisms underlying the subversion of macrophage signaling and functions.